Analisis Pengaruh Internet Marketing terhadap Pembentukan Word of Mouth dan Brand Awareness untuk Memunculkan Intention to Buy - Richard Darmawan Andriyano, Jony Oktavian Haryanto (ITB, 2010)
The purposes of this research are to prove whether internet marketing does give postive influence to the formation of brand wareness and word of mouth, then whether if internet marketing is directly give positive influence to formation of intention to buy. Furthermore, the writerwants to analyze therelationship between brand awareness and word of mouth to create intention to buy. The data was analyzed using structural equation modeling with amos software. Sample of this research was 130 respondents who are taken by judgment sampling. This research found that internet marketing positively to buy. Brand awareness also does not gibe positive influence to word of mouth. Both brand awareness and word of mouth do infulence positively to formation of intention to buy